2020
DOI: 10.3390/cells9030708
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Nfix Requires RhoA-ROCK1 Dependent Phagocytosis to Mediate Macrophage Skewing during Skeletal Muscle Regeneration

Abstract: Macrophages (MPs) are immune cells which are crucial for tissue repair. In skeletal muscle regeneration, pro-inflammatory cells first infiltrate to promote myogenic cell proliferation, then they switch into an anti-inflammatory phenotype to sustain myogenic cells differentiation and myofiber formation. This phenotypical switch is induced by dead cell phagocytosis. We previously demonstrated that the transcription factor Nfix, a member of the nuclear factor I (Nfi) family, plays a pivotal role during muscle dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 62 publications
2
45
1
Order By: Relevance
“…We observed an increase in the number of MPs expressing Nfix in both TA and Dia muscles of the mdx and Sgca null mice between 2 and 6 months of life (Figure 1a and b). During muscle regeneration after acute injury, we showed that Nfix is required for Ly6Canti-inflammatory phenotype acquisition 27 . Although the concept of pro-and anti-inflammatory MPs does not seem to be conserved between acute and chronic muscle injury context, we still decided to look at the number CD64 + MPs positive for Nfix within the Ly6C + and Ly6Cpopulation sorted from the TA of Sgca null mice.…”
Section: Dystrophymentioning
confidence: 94%
See 2 more Smart Citations
“…We observed an increase in the number of MPs expressing Nfix in both TA and Dia muscles of the mdx and Sgca null mice between 2 and 6 months of life (Figure 1a and b). During muscle regeneration after acute injury, we showed that Nfix is required for Ly6Canti-inflammatory phenotype acquisition 27 . Although the concept of pro-and anti-inflammatory MPs does not seem to be conserved between acute and chronic muscle injury context, we still decided to look at the number CD64 + MPs positive for Nfix within the Ly6C + and Ly6Cpopulation sorted from the TA of Sgca null mice.…”
Section: Dystrophymentioning
confidence: 94%
“…Since MPs are linked to MDs 11,20,28 and as we demonstrated a pivotal function of Nfix in MPs function during muscle regeneration 27 , we decided to analyze the number of Nfix + MPs during the progression of MD within the Tibialis Anterior (TA) and diaphragm (Dia) of two different dystrophic murine models (the mdx and the Sgca null mice). We observed an increase in the number of MPs expressing Nfix in both TA and Dia muscles of the mdx and Sgca null mice between 2 and 6 months of life (Figure 1a and b).…”
Section: Dystrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Resolution of inflammation is characterized by a progressive switch of the inflammatory profile exhibited by macrophages, that become anti-inflammatory or recovery macrophages. This process is controlled by several molecular effectors, including the metabolic sensor AMPK (Mounier et al, 2013), the IGF1 pathway (Tonkin et al, 2016), the p38 regulator MKP-1 (Perdiguero et al, 2011), and the transcription factors C/EBPβ (Ruffell et al, 2009) and NFIX (Saclier et al, 2020). These anti-inflammatory macrophages exert a variety of effects on surrounding cells: they stimulate the last steps of myogenesis, including differentiation and fusion (Saclier et al, 2013), they activate FAPs to remodel the extracellular matrix (ECM) (Juban et al, 2018; Lemos et al, 2015), and favor angiogenesis, which occurs concomitantly to myogenesis (Latroche et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor Nfix, a member of the nuclear factor I (Nfi) family, plays a pivotal role during muscle development, regeneration and in the progression of muscular dystrophies. Saclier, et al, showed that Nfix is mainly expressed by anti-inflammatory macrophages [14]. Upon acute injury, mice deleted for Nfix in myeloid line displayed a significant defect in the process of muscle regeneration.…”
mentioning
confidence: 99%